Crescimento de cultivares de cafeeiro conilon submetidas ao estresse salino-hídrico - da Silva Temoteo, Amansleone [UNESP]; de Padua Sousa, Antônio [UNESP]; dos Santos, Cícero Manoel [UNESP]; Teramoto, Érico Tadao [UNESP] (My University, 2015)
The culture of coffee is quite important on the national scene and in the country's economy. Though, the crop response to salt stress is not well known. The objective of this paper was to evaluate compar-atively the initial growth of seedlings of two Conilon coffee cultivars under different conditions of soil salinity, and low water availability in the soil. The experiment followed a randomized block design in factorial arrange-ment with two Conilon cultivars (clones 120 and 14), two levels of water in the soil (50% and 70% of available soil water) and four levels of soil salinity (0; 2.0; 4.0 and 6.0 dS m-1). The physiological characteristics of growth: leaf area (Area F), stem height (Height. C), Stem diameter (Dia. C), reproductive branches numbers, shoot biomass and root were evaluated. Among the growth variables, leaf area and leaf dry mass and root are the best indicators of the presence of saline-hydric stress. The cultivar clone 120 is moderately tolerant of soil salinity, with less reduction in leaf area and leaf dry mass when subjected to salt stress.
Growth conilon coffee cultivars subjected to saline-hidric stress
Keywords: Coffea canephora; Soi salinity; Wate deficit